High Level of Knowledge about Tungiasis but Little Translation into Control Practices in Karamoja, Northeastern Uganda - Marlene Thielecke; Hannah McNeilly; Francis Mutebi; Mike B. Banalyaki; Rebecca Arono; Susanne Wiese; Felix Reichert; George Mukone; Hermann Feldmeier (Tropical Medicine and Infectious Disease, 2023)
Tungiasis is a neglected tropical disease (NTD) that can cause significant suffering and disability. Health promotion is an important pillar in NTD control programs, assuming that better knowledge contributes to reduced risk behavior and reduced risk of infection. The study objective was to assess tungiasis-related knowledge and its translation into control practices in a rural and highly endemic setting in Karamoja, Northeastern Uganda. We applied a mixed-methods design on household and community level. A semi-quantitative questionnaire on knowledge, practices, and attitudes (KAP) regarding tungiasis was administered to 1329 individuals with the main caring responsibilities in the household. Additionally, eight community dialogue meetings were held and analyzed. Overall, knowledge of tungiasis in humans was high but knowledge of tungiasis in animals was low. Most questionnaire respondents knew the causative agent and clinical presentations of tungiasis in humans, risk factors, and preventive measures. This tungiasis-related knowledge was translated into simple prevention measures. However, adequate tungiasis control was impeded due to a lack of resources, such as access to water and effective medical treatment. In conclusion, health promotion campaigns should be integrated with support towards adequate tungiasis control measures, such as provision of safe treatment, hardening of non-solid floors in the houses, and improved access to water.